MICROORGANISM PROFILE OF TEETH AND ORAL CAVITY DISORDER IN ELDERLY POPULATION - Puspa W Suryantarini; Ni Wayan Puspa Wijaya Suryantarini (University of Mataram, 2025)
The increase in the elderly population is accompanied by an increase in the prevalence of associated dental and oral diseases. The elderly’s susceptibility to these conditions is influenced by factors such as dental and oral hygiene, lifestyle, and underlying medical conditions. In order to effectively manage dental and oral infections, identifying the causative pathogens by medical teams is crucial. A literature review conducted between 2020 and 2025 was conducted to determine the profile of bacterial microorganisms involved in dental caries and gingivitis infections in the elderly. The literature search identified 8 sources for further review. In general, dental caries and gingivitis infections in the elderly are not significantly different from those in children and adults. Bacterial species vary, including both gram-positive and gram-negative bacteria. Most bacteria are resistant to several antibiotics, so microbiological and antibiotic sensitivity testing are essential for selecting appropriate treatment. Preventive measures are also essential in comprehensive care. The elderly should be supported to practice good dental and oral hygiene, maintain a healthy diet, and manage any systemic diseases they may have.